Digital Entrepreneurship Assistance for Handicraft SMEs in Cileng Village - Aviyanti, Richo Diana; Widiasmara, Anny; Devi, Heidy Paramitha; Nurhayati, Puji; Chairunnisa, Diaz Martha; Zami, Moh. Tajuddin Azzam (International Journal of Community Service Learning, 2022)
The increase in the number of MSMEs will not contribute and support them if they cannot compete with the changing times. Internet of Things (IoT) is one form of changing times that impacts all aspects, including business. The impact of IoT on business is the existence of businesses, from conventional businesses to digital businesses. MSMEs must respond to these business changes, one of which is by changing conventional marketing to digital marketing. This activity aims to increase literacy on marketing strategies and information technology, develop marketing reach, and increase turnover. The target of this PKM program is a group of MSMEs producing handicrafts in Cileng Village, Magetan, which still lacks literacy about marketing and information technology. The method of service is mentoring and training. Mentoring and training related to product photos, making product descriptions using copywriting techniques, and opening an online store. The program is expected to increase knowledge about digital marketing training, market reach, and meeting the desired turnover target. Moreover this community service potential for the development of Creative Economy-based SMEs.